Realism for the masses : aesthetics, popular front pluralism, and U.S. culture, 1935-1947 - Vials, Chris (Book collections on Project MUSE., 2009)
Realism for the Masses, is an exploration of how the concept of realism entered mass culture, and from there, how it tried to remake?America.? The literary and artistic creations of American realism are generally associated with the late nineteenth century. But this book argues that the aesthetic actually saturated American culture in the 1930s and 1940s and that the left social movements of the period were in no small part responsible. The book examines the prose of Carlos Bulosan and H.T. Tsiang; the photo essays of Margaret Bourke-White in Life magazine; the bestsellers of Erskine Caldwel.